Organizational Culture in the Digital Workplace: A Bibliometric Review - Loso Judijanto (West Science Social and Humanities Studies, 2026)
This paper explores the evolving relationship between organizational culture and digital transformation through a bibliometric review of the existing literature. The study aims to map the key research themes, trends, and emerging gaps in the field, focusing on how digital technologies are reshaping organizational culture, leadership, and employee engagement. By conducting a bibliometric analysis of academic articles published in the last two decades, this review identifies "digital transformation," "organizational culture," and "workplace" as central themes of recent research. The study also highlights the growing importance of leadership in managing digital workplaces and the need for adaptive organizational cultures that foster innovation and collaboration in remote and hybrid environments. Furthermore, the paper identifies several underexplored areas, particularly the emotional and social aspects of digital transformation, such as employee well-being, psychological safety, and identity within digital workspaces. The findings provide valuable insights for both academics and practitioners interested in understanding the complexities of fostering a positive organizational culture in the digital age.